2011
DOI: 10.1186/1471-2407-11-166
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal embryonal rhabdomyosarcoma in an adult - A case presentation in the eyes of geneticists and clinicians

Abstract: 1. AbstractBackgroundRhabdomyosarcoma is a solid tumor, resulting from dysregulation of the skeletal myogenesis program. For rhabdomyosarcomas (RMS) with a predilection for the head and neck, genitourinary tract, extremities, trunk, retroperitoneum, the larynx is still an unusual site. Till now only several cases of this laryngeal tumor have been described in world literature in the adult population. The entire spectrum of genetic factors underlying RMS development and progression is unclear until today. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Embryonal rhabdomyosarcoma of the adult larynx has been poorly described, with only 4 cases identified in the literature to our knowledge [1,2,6,7]. In general, it is a poorly described lesion that should be managed aggressively via a multi-disciplinary approach, with strong consideration for total laryngectomy if necessary to obtain clear margins when organ preservation surgery, partial laryngectomy, is not feasible.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Embryonal rhabdomyosarcoma of the adult larynx has been poorly described, with only 4 cases identified in the literature to our knowledge [1,2,6,7]. In general, it is a poorly described lesion that should be managed aggressively via a multi-disciplinary approach, with strong consideration for total laryngectomy if necessary to obtain clear margins when organ preservation surgery, partial laryngectomy, is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have suggested a range of therapeutic modalities for embryonal rhabdomyosarcoma of the adult larynx (Table 1). A recent case describes a 33 year old male who presented with hoarseness and ultimately required a vertical hemilaryngectomy due to lack of regression despite induction and concommitant chemoradiation with VAC and 7000 cGy over 6 weeks [2]. Alternatively, other authors describe a case of embryonal rhabdomyosarcoma in the submucosa of the ventricular band that responded completely to cisplatin, vincristine, doxorubicin, and cyclophosphamide with radiation following induction chemotherapy [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations